Diálogos entre as artes, a educação e a história: considerações a partir das produções de Luís Gama e de Rosana Paulino - Costa, Thays Alves; Ribeiro, Diego (Farol, 2022)
This article explores the dialogue between arts, education and history, contemplating the historical and critical dimensions of Rosana Paulino and Luís Gama productions. The first, a contemporary artist, presents her works using direct references to the history of Brazil, as a kind of denunciation and historical reparation from our violent and regrettable past in the context of slavery. The lawyer and poet Luís Gama was one of the important characters in the Brazilian abolitionist movement, being one of those responsible for establishing legal strategies for the liberation of the enslaved, in addition to that he developed a rich literary work, such as book of poems: As Primeiras Trovas Burlescas de Getulino, from 1859. Thus, this article will present the act of resistance through Luís Gama’s poetry and the desire for reparation in the art of Rosana Paulino, demonstrating the importance of studying these characters in basic education.